A simple method for preparing chelated calcium based on the black liquor generated by the pulp and paper industry. Issue 1 (1st January 2019) - Yang, Guiting; Cheng, Donghong; Liu, Yan; Dongdong, Cheng; Zhang, Min; Zhao, Hongmeng; Sun, Yao; Huang, Songjun; Sao, Junfei; Xu, Ting; Huang, Xiancheng
ABSTRACT: A simple method for preparing chelated calcium from black liquor produced in the paper industry was studied. Various factors influencing the chelation rate of Ca 2+ were studied, including the system pH, reaction temperature, reaction time, reaction solution ratio. The optimum reaction conditions are as follows: the system pH, reaction temperature, reaction solution ratio (V(CaCl2 ):m (Black liquor)) and time were 5.6, 25°C, 1:20 and 60 min, respectively. The maximum Ca 2+ chelation rate was 88.75%. The characteristics of chelated calcium fertilizer in black liquor were studied by Fourier transform infrared, scanning electron microscope . The results indicated that the CaCl2 could be chelated by the black liquor from paper-making industry, and showed a high chelating rate.